Capacity Fade in Solid-State Batteries: Interphase Formation and Chemomechanical Processes in Nickel-Rich Layered Oxide Cathodes and Lithium Thiophosphate Solid Electrolytes - Koerver, Raimund; Aygün, Isabel; Leichtweiß, Thomas; Dietrich, Christian; Zhang, Wenbo; Binder, Jan O; Hartmann, Pascal; Zeier, Wolfgang G; Janek, Jürgen (Chemistry of materials, 2017)
All-solid-state lithium ion batteries may become long-term, stable, high-performance energy storage systems for the next generation of electric vehicles and consumer electronics, depending on the compatibility of electrode materials and suitable solid electrolytes. Nickel-rich layered oxides are nowadays the benchmark cathode materials for conventional lithium ion batteries because of their high storage capacity and the resulting high energy density, and their use in solid-state systems is the next necessary step. In this study, we present the successful implementation of a Li[Ni,Co,Mn]O2 material with high nickel content (LiNi0.8Co0.1Mn0.1O2, NCM-811) in a bulk-type solid-state battery with β-Li3PS4 as a sulfide-based solid electrolyte. We investigate the interface behavior at the cathode and demonstrate the important role of the interface between the active materials and the solid electrolyte for the battery performance. A passivating cathode/electrolyte interphase layer forms upon charging and leads to an irreversible first cycle capacity loss, corresponding to a decomposition of the sulfide electrolyte. In situ electrochemical impedance spectroscopy and X-ray photoemission spectroscopy are used to monitor this formation. We demonstrate that most of the interphase formation takes place in the first cycle, when charging to potentials above 3.8 V vs Li+/Li. The resulting overvoltage of the passivating layer is a detrimental factor for capacity retention. In addition to the interfacial decomposition, the chemomechanical contraction of the active material upon delithiation causes contact loss between the solid electrolyte and active material particles, further increasing the interfacial resistance and capacity loss. These results highlight the critical role of (electro-)chemo-mechanical effects in solid-state batteries.